ANALISIS ZALIR KERA PADA PEMBANGKIT LISTRIK TENAGA OTEC (OCEAN THERMAL ENERGI CONVERSION) - Andi Hendrawan; Lusiani; Aris Sasongko (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
The potential difference in sea temperature between the surface and subsurface beneath the thermocline that can be converted into electrical energy has been investigated using ocean temperature data OTEC power plant is very suitable as a provider of electric power for the archipelago. The archipelagic country does have many obstacles in terms of energy distribution. The long distance between islands adds to the burden of energy transportation financing. OTEC power plant design is very concerned about various important things, one of the most important thing is the design of a kettle or boiler.The heat difference so small makes the kettle must be designed strictly and correctly. the purpose of this study is to compare the working fluid used in the OTEC plant. based on various literature studies show there are some working fluid that can be used in OTEC generating system such as ammonia, hydrogen, propane, R77. The most advantageous working fluid is if we use mixed fluid because of its high efficiency so that it can produce high electrical power as well.